Modelo conceitual de controle orçamentário à luz do GECON em empresas de pequeno porte: estudo de caso - Linhares, Eduardo Rodrigues (2005)
This work has an aim to verify the applicability of a budget plan, proposed by GECON, acting as an instrument that helps the manager to get the expected results for his products, electing the economic result as a valuator of taken decisions, aiming the correction of directions which take to the accomplishment of an expected goal, in terms of results. The Method used in this research was a deduction one, setting up as a methodologic objective a describing investigation, using the proceedings in a Study of Case. It was chosen a small company to inform about the universe of the problem-situation. For this, it was developed a qualitative approach. In relation to GECON’s model, it is said, by this work, that it is a very good tool, provided that it’s able to identify the inflation variations and very useful in plans adjustment, volumes, efficiency and prices, giving to the manager a detailed report, in monetary terms, concern on possible deviations, helping a pro-active behavior from the manager’s part. This study analyses standards, as an physical terms as in a monetary aspect, their alternations and how they influence in the process of reaching goals in the business world. This work proposes a price-index, an internal one, specifical for the company, considering the reality in which it is inserted. The present works reputes GECON’s model as the best one to satisfy the manager’s information needs, according to conclusions taken during the stages of the research adjoining the studied company. Key